1990
DOI: 10.1002/ana.410280520
|View full text |Cite
|
Sign up to set email alerts
|

Absence of immunoreactive enzyme protewin in short‐chain acylcoenzyme a dehydrogenase deficiency

Abstract: Defects of short-chain acylcoenzyme A dehydrogenase (SCAD) may cause a severe metabolic illness in children or a lipid storage myopathy in adults. The childhood form is associated with low enzyme activity, but the synthesis of a normal-size enzyme protein in cultured skin fibroblasts. We report further biochemical studies on the original patient described with myopathic SCAD deficiency. We show an absence of enzyme protein in skeletal muscle, which both confirms the original diagnosis and suggests that the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

1992
1992
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…Although Turnbull et a/. (9) and Farnsworth et al (10) reported a human patient with apparent muscular SCAD deficiency, our observations argue against the presence of tissue-specific SCAD isoforms in mammals.…”
contrasting
confidence: 68%
See 2 more Smart Citations
“…Although Turnbull et a/. (9) and Farnsworth et al (10) reported a human patient with apparent muscular SCAD deficiency, our observations argue against the presence of tissue-specific SCAD isoforms in mammals.…”
contrasting
confidence: 68%
“…Carole Hall and potential explanation for the biochemical findings in this patient Colin Thorpe for provision of the pure enzymes and Dr. Kay would involve a mutation of a muscle-specific SCAD isozyme, Tanaka for his advice and support. although there is no direct evidence to support this possibility (9,10). We found that fibroblasts from this patient had normal REFERENCES SCAD and MCAD activities and oxidized both [9'10(n)-…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…It has been documented previously that some patients have an absence of immunoreactive protein in their cells and that there are mutations that appear to affect folding in a temperature-sensitive manner (41)(42)(43). The mutations either disrupt hydrogen bonding or salt bridge networks and/or disrupt local topology by the introduction of a bulky amino acid side chain, thus affecting monomer folding and oligomer formation.…”
Section: Fig 3 Stereo Diagram Of Acetoacetyl-coa and Amino Acid Resmentioning
confidence: 99%
“…There seem to be two forms : first, a severe infantile systemic form [106,107] ; and secondly, a mild, late-onset phenotype with predominantly muscle involvement [105,108]. The disorder is not expressed in the fibroblasts of patients with the muscle phenotype but is in the infantile variant [109].…”
Section: Scad Deficiencymentioning
confidence: 99%